Radiation exposure during coronary angiography via transradial or transfemoral approaches when performed by experienced operators - Shah, Binita (2013)
BACKGROUND: Studies demonstrate an increase in radiation exposure with transradial approach (TRA) when compared with transfemoral approach (TFA) for coronary angiography. Given the learning curve associated with TRA, it is not known if this increased radiation exposure to patients is seen when procedures are performed by experienced operators. METHODS: We retrospectively evaluated 1,696 patients who underwent coronary angiography with or without percutaneous coronary intervention (PCI) by experienced operators at a tertiary center from October 2010 to June 2011. Experienced operators were defined as those that perform >75 PCIs/year with >95% of cases performed using the TRA or TFA approach for ≥5 years. The outcomes of interest were dose area product (DAP) and fluoroscopy time (FT). RESULTS: Of the 1,696 patients, 1,382 (81.5%) were performed by experienced femoral operators using TFA and 314 (18.5%) were performed by experienced radial operators using TRA. Most of these cases (65.4%) were diagnostic only (870 TFA and 240 TRA) with both DAP (6040 [3210–8786] vs 5019 [3377–6869] μGy·m(2), P = .003] and FT [6.2 [4.0–10.3] vs 3.3 [2.6–5.0] minutes, P < .001) significantly higher using TRA versus TFA. For procedures involving PCI, despite similar baseline patient, procedural and lesion characteristics, DAP and FT remained significantly higher using TRA versus TFA (19,649 [11,996–25,929] vs 15,395 [10,078–21,617] μGy·m(2), P = .02 and 22.1 [13.3–31.0] vs. 13.8 [9.8–20.3] minutes, P < .001). CONCLUSIONS: In a contemporary cohort of patients undergoing coronary angiography by experienced operators, TRA was associated with higher radiation exposure when compared with TFA.